Recurrent Laryngeal Nerve Injury between Identification Nerve and Capsular Technique of Thyroidectomy - ช่วยแก้ว ปนัดดา (Journal of Health Science of Thailand, 2022)
After thyroid surgery, recurrent laryngeal nerve injury can occur. The aim of this study was to compare the incidence and risk of recurrent laryngeal nerve injury during thyroidectomy with non-nerve identification technique versus nerve identification technique. The methodology used was a randomized controlled trial. There were 140 participants in the study. The primary outcome of interest was the risk of recurrent laryngeal nerve injury when compared between the non-nerve identification and nerve identification technique. The results showed that thyroidectomy with non-nerve identification technique compared with nerve identification technique in this study had an incidences of 10.00% and 8.57%, respectively. In addition, thyroid surgery with non-nerve identification technique had no different risk of recurrent laryngeal nerve injury than thyroid surgery with nerve identification technique (RR=1.17, 95%CI=0.41-3.30).